A Comparison of Various Methods of Measuring Antidepressant Medication Adherence Among Children and Adolescents with Major Depressive Disorder in a 12-Week Open Trial of Fluoxetine - Nakonezny, Paul A. (Mary Ann Liebert, Inc., 2010)
OBJECTIVE: In this study, we examined antidepressant (fluoxetine) medication adherence in children and adolescents with major depressive disorder (MDD). Using electronic monitoring (EM) as the “reference standard,” we compared various methods of measuring antidepressant medication adherence (including EM, pill counts, and medication diaries) among children and adolescents with MDD and examined the relationship between EM medication adherence and depression severity across time. We then suggested recommendations for clinical researchers and practicing clinicians regarding medication adherence assessment. METHOD: Thirty-one child and adolescent outpatients with MDD who enrolled in a 12-week open trial of fluoxetine had their antidepressant medication adherence assessed at each visit, using EM, pill counts, and parent and patient medication diaries. Depression severity was assessed by the Children's Depression Rating Scales—Revised at each visit. RESULTS: Twelve-week least squares mean estimates of medication adherence for the entire sample was high, regardless of the adherence assessment method, although the overall adherence among the four methods (EM, pill, parent diary, patient diary) was significantly different (87.5% vs. 90.6% vs. 93.1% vs. 93.3%, respectively, p = 0.0002). Adjusted mean symptom severity was significantly lower for the EM “adherent” group than for the EM “nonadherent” group over the 12 weeks of treatment (35.6 vs. 43.8, p = 0.008). CONCLUSION: Overall, EM medication adherence for the depressed youth in this study is high. Compared with EM, there is a tendency of pill counts and medication diaries to overestimate medication adherence. However, pill count adherence better approximates EM adherence, and compliance with returning medication diaries is poor. Youth who are adherent to fluoxetine treatment have lower symptom severity over the course of treatment. Recommendations are provided.